2003
DOI: 10.1034/j.1600-0706.2003.12424.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between above‐ and belowground insect herbivores as mediated by the plant defense system

Abstract: Plants are frequently attacked by both above‐ and belowground arthropod herbivores. Nevertheless, studies rarely consider root and shoot herbivory in conjunction. Here we provide evidence that the root‐feeding insect Agriotes lineatus reduces the performance of the foliage feeding insect Spodoptera exigua on cotton plants. In a bioassay, S. exigua larvae were allowed to feed on either undamaged plants, or on plants that had previously been exposed to root herbivory, foliar herbivory, or a combination of both. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
172
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 45 publications
2
172
2
3
Order By: Relevance
“…Induction of secondary metabolites in roots due to root feeding by insect larvae has been reported for a number of plant and herbivore combinations (Birch et al 1992;Bezemer et al 2003Bezemer et al , 2004Borowicz et al 2003;Van Dam and Raaijmakers 2006) and might be a general plant response similar to aboveground induction due to shoot herbivores (Karban and Baldwin 1997). Irrespective of plant line, wireworms had no significant effect on root biomass, but led to an increase in leaf biomass, pointing to compensatory shoot growth (Wurst and Van der Putten 2007).…”
Section: Discussionmentioning
confidence: 83%
“…Induction of secondary metabolites in roots due to root feeding by insect larvae has been reported for a number of plant and herbivore combinations (Birch et al 1992;Bezemer et al 2003Bezemer et al , 2004Borowicz et al 2003;Van Dam and Raaijmakers 2006) and might be a general plant response similar to aboveground induction due to shoot herbivores (Karban and Baldwin 1997). Irrespective of plant line, wireworms had no significant effect on root biomass, but led to an increase in leaf biomass, pointing to compensatory shoot growth (Wurst and Van der Putten 2007).…”
Section: Discussionmentioning
confidence: 83%
“…For instance, Kaplan et al [11] found in tobacco that root-feeding nematodes increased the performance of folivorous caterpillars by blocking synthesis of alkaloids that are transported to leaves, but caterpillars increased nematode performance by increasing nitrogen transport to roots. In cotton, root-feeding wireworms decreased foliar caterpillar performance by increasing foliar terpenoid levels, but caterpillars had no effect on wireworm performance [16]. In barley, root-feeding wireworms increased foliar aphid reproduction by increasing essential amino acids in leaves, but aphids increased wireworm mass by increasing root mineral content [13].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that other nematodes (e.g., fungal feeders, bacterial feeders) may, however, also indirectly affect plant-insect interactions by interacting with other soil organisms. Plantparasitic nematodes, by feeding on the roots of shared host plants, can influence the defense status and nutritional quality of host plants, potentially leading to effects on herbivores (Bezemer et al, 2003;Bezemer and van Dam, 2005;Wondafrash et al, 2013;Biere and Goverse, 2016). Results from laboratory studies of the effects of plant-parasitic nematodes on aboveground insects are often variable for chewing insects, but generally show negative effects on either the performance or preference of sap sucking insects (Johnson et al, 2012;Wondafrash et al, 2013).…”
Section: Nematodesmentioning
confidence: 99%